Heavy Meromyosin: Evidence for a Refractory State Unable to Bind to Actin in the Presence of ATP - Eisenberg, Evan (1972)
The binding of actin to heavy meromyosin (HMM) in the presence of ATP was studied by analytical ultracentrifuge and ATPase studies. At 0°C, at very low ionic strength, the double-reciprocal plot of HMM ATPase against actin concentration is linear. If one assumes that all of the HMM is bound to actin when the ATPase activity equals V(max), then, at an actin concentration where the actin-HMM ATPase is 85% of V(max), all but 15% of the HMM should be complexed with actin. However, when the binding of HMM to actin in the presence of ATP was measured with the analytical ultracentrifuge, more than 60% of the HMM was not bound to actin. From experiments with EDTA- and Ca-ATPases it seemed unlikely that the unbound HMM was denatured. It is thus possible that during the steady-state hydrolysis of ATP, HMM spends more than 50% of its cycle of interaction with actin and ATP in a “refractory state,” unable to bind to actin, i.e., while an HMM molecule goes through one cycle of interaction with actin and ATP, an actin monomer could bind and release several HMM molecules so that the turnover rate per mole of added actin would be considerably greater than that per mole of added HMM. Comparison of the rate of ATPase activity at very high actin concentration with that at very high HMM concentration shows that this is indeed so. Therefore, both kinetic and ultracentrifuge studies suggest that the HMM exists in a refractory state during a large part of its cycle of interaction with actin and ATP.